Testing the gauged U(1)B–L model for loop induced neutrino mass with dark matter* - Ying Guohao; Kanemura Shinya; Mura Yushi (EPJ Web of Conferences)
We present a new viable benchmark scenario under the current experimental data for the model which can explain tiny mass of active neutrinos and dark matter, as a summary of Ref. [1]. Majorana masses of right-handed neutrinos are given by the spontaneous breaking of the U(1)B−L gauge symmetry above the electroweak scale, and tiny neutrino masses are radiatively induced by quantum effects of particles of the dark sector including dark matter candidates. We first show benchmark points which satisfy current experimental data, and then give comments on how this model can be tested at collider experiments.